Dietary Proportion of Protein from Plant Sources in Relation to the Risk of Incident Chronic Kidney Disease in Korean Adults: The Health Examinees (HEXA) Study (P18-083-19). (13th June 2019) - Na, Woori; Park, Susan; Sohn, Cheongmin
Abstract: Objectives: Diet is an important determinant of chronic kidney disease (CKD) development. The purpose of this study was to evaluate the association of proportion of dietary protein from plant sources with the risk of incident CKD in a population-based prospective study. The purpose of this study was to evaluate the association of proportion of dietary protein from plant sources with the risk of incident CKD in a population-based prospective study. Methods: This study analyzed data from the Health Examinee (HEXA) cohort of the Korean Genome and Epidemiology Study (KoGES) between 2005 and 2012 for 148, 534 individuals who were initially free of CKD and aged 40–69 years. Baseline diet was assessed by a validated FFQ. Estimated glomerular filtration rate (eGFR) was calculated, using the CKD–EPI equation, and CKD was defined as eGFR < 60 ml/min per 1.73 m2. Multivariate Cox proportional hazard models were used to examine the risk for incident according to dietary proportion of protein from plant sources. Results: The mean of plant protein-total protein ratio was 59.1 ± 13.52%. There were 1041 cases of incident CKD over a median of 6.41 years of follow-up. After adjustment for demographic, clinical and dietary factors, the highest quartile of a proportion of dietary protein from plant sources was significantly associated with the development of incident CKD (HR comparing fourth to first quartile, 0.738; 95%CI, 0.583–0.933) in men, but not in women. Conclusions: We observed that a diet with higher proportion of protein from plant sources is associated with decreased risk of incident CKD in men. This study provides evidence suggesting a potential protective effect of plant protein sources against the development of CKD. Funding Sources: N/A.